2002
DOI: 10.1007/s00247-002-0779-3
|View full text |Cite
|
Sign up to set email alerts
|

Lap belt iliac wing fracture: a predictor of bowel injury in children

Abstract: Lap belt restraints in motor vehicle collisions have been associated with a variety of injuries, mainly bowel and lumbar spine. Cephalad positioning of the belt over the intended position across the anterior superior iliac spines (which typically occurs in younger children) is thought to be responsible for the observed bowel injuries. We report two pediatric patients, both restrained by lap belts in high-speed collisions, who suffered iliac wing fractures in addition to bowel injuries. Unexplained free periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…During NCAP tests, anthropomorphic dummies are secured into the vehicle by safety belts and vehicles are crashed into a fixed barrier at will be applied across the pelvis as a result. Occasionally this force results in fracture of the iliac wing which has been described in both adults (Greenbaum and Rolston, 1971) and children (Emery, 2002), and may be associated with other seatbelt related injuries such as hollow viscus injury (Emery, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…During NCAP tests, anthropomorphic dummies are secured into the vehicle by safety belts and vehicles are crashed into a fixed barrier at will be applied across the pelvis as a result. Occasionally this force results in fracture of the iliac wing which has been described in both adults (Greenbaum and Rolston, 1971) and children (Emery, 2002), and may be associated with other seatbelt related injuries such as hollow viscus injury (Emery, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric studies of this topic primarily consist of case series or retrospective reviews. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] A single-center prospective study demonstrated an association between the seat belt sign and intra-abdominal injury in children, but was limited by its small sample size. 25 In contrast, one pediatric study failed to demonstrate any association between the seat belt sign and intra-abdominal injury.…”
Section: Discussionmentioning
confidence: 99%